Bacteroides dorei BDX-01 alleviates DSS-induced experimental colitis in mice by regulating intestinal bile salt hydrolase activity and the FXR-NLRP3 signaling pathway - Sun, Xiaowei; Chen, Zhenhui; Yu, Lu; Zeng, Weisen; Sun, Boyuan; Fan, Hongying; Bai, Yang (Frontiers in Pharmacology, 2023)
Background: The relationships among intestinal dysbiosis, bile acid (BA) metabolism disorders, and ulcerative colitis pathogenesis are now recognized. However, how specific strains regulate BA metabolism to alleviate colitis is still unclear. This study investigated the effects of Bacteroides dorei on the development of acute colitis and elucidated the underlying mechanisms. Methods: The safety of BDX-01 was evaluated in vitro and in vivo. 2.5% dextran sulfate sodium (DSS) induced colitis in C57BL/6 mice, Caco-2 and J774A.1 cells were used to evaluate the anti-inflammatory effect of BDX-01. qPCR and Western blotting were used to detect the expression of inflammatory pathways. Microbiota composition was analyzed by 16S rRNA gene sequencing. Enzyme activity analysis and targeted metabolomics were used to analyze fecal bile salt hydrolase (BSH) and BA levels. Antibiotic-induced pseudo-germ-free mice were used to investigate the role of gut microbiota in the alleviation of colitis by BDX-01. Results: We confirmed the safety of novel strain Bacteroides dorei BDX-01 in vitro and in vivo. Oral BDX-01 administration significantly ameliorated the symptoms and pathological damage of DSS-induced acute colitis. Moreoever, 16S rRNA sequencing and enzyme activity analysis showed that BDX-01 treatment increased intestinal BSH activity and the abundance of bacteria harboring this enzyme. Targeted metabolomics revealed that BDX-01 significantly increased intestinal BA excretion and deconjugation. Certain BAs act as FXR agonists. The β-muricholic acid (βMCA): taurine β-muricholic acid (T-βMCA) and cholic acid (CA): taurocholic acid (TCA) ratios and the deoxycholic acid (DCA) level decreased markedly in the colitis models but increased substantially in BDX-01-treated mice. The colonic farnesoid X receptor (FXR) and fibroblast growth factor 15 (FGF-15) were upregulated in mice treated with BDX-01. BDX-01 downregulated the expression of colonic proinflammatory cytokines pyrin domain-containing 3 (NLRP3) , ASC, caspase-1, p20, and IL-1β. Antibiotic treatment didn’t abolish the protective effect of BDX-01 on colitis. In vitro studies showed TβMCA abolished the effects of BDX-01 on FXR activation and inhibition of the NLRP3 inflammasome activation. Conclusions: BDX-01 improved DSS-induced acute colitis by regulating intestinal BSH activity and the FXR-NLRP3 signaling pathway. Our findings indicate that BDX-01 is a promising probiotic to improve the management of ulcerative colitis.